PENGARUH OPERATION CASH FLOW, EARNING PER SHARE, RETURN ON ASSETS, RETURN ON EQUITY DAN TAX PLANNING TERHADAP RETURN SAHAM (Studi Empiris Pada Perusahaan Manufaktur Yang Masuk LQ45 di Bursa Efek Indonesia Tahun - benny frastiawan ahmad putra (JURNAL EKOBIS DEWANTARA, 2018)
This study aims to examine the effect of Operation Chas Flow (OCF), Earning Per Share (EPS), Return On Assets (OCF), Return On Equity (ROE), and Tax Planning to Return Shares In Manufacturing Companies Entry LQ45 Index in Stock Exchange Indonesia Year 2012 - 2016. The sampling technique used purposive sampling with the number of samples of eight companies. The data used in this research is obtained from the Financial Statement obtained from the Indonesia Stock Exchange website. Data analysis method used is multiple linear regression with SPSS 16.0. Based on the results of the test, the results obtained simultaneously Operation Chas Flow (OCF), Earning Per Share (EPS), Return On Assets (OCF), Return On Equity (ROE), and Tax Planning effect on Return Share with significant value 0.014, partially Earning Per Share (EPS) has a significant positive effect with significant value of 0.001. Operation Chas Flow (OCF), Return On Assets (OCF), Return On Equity (ROE), and Tax Planning have no effect on Stock Return.